Strengthening Islamic Character Education through Uswah Hasanah and Religious Maturity in Ma’had Al-Jami’ah - Mukminin, Amir; Ratih, Ratih; Sugiyo, Sugiyo; Hasyim, Dardiri (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
Islamic character education plays a crucial role in supporting the moral and spiritual development of students in Islamic higher education institutions. This study aims to analyze the influence of uswah hasanah and religious maturity on Islamic character education among students at Ma’had Al-Jami’ah Ulil Abshar Ponorogo. The research employed a quantitative survey design, involving 200 students selected through stratified random sampling. Data were collected using a questionnaire that had been tested for validity and reliability, and analyzed using multiple linear regression. Classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation, were conducted before regression analysis. The results indicate that uswah hasanah has a positive and significant partial effect of 44,1% on Islamic character education, while religious maturity contributes a positive and significant effect of 41,5%. Simultaneously, both variables explain 56,4% of the variance in students’ Islamic character education, with the remaining 43,6% influenced by factors outside the study. These findings highlight the importance of exemplary behavior and religious maturity as key determinants of Islamic character formation and emphasize the need for a holistic approach integrating religious, social, and everyday experiential aspects in character development.